Aktifitas Perdagangan Lokal di Kepualuan Maluku Abad 15 M - 19 M, Tinjauan Awal Berdasarkan Data Keramik Asing dan Komoditas Lokal - Wuri Handoko (Balai Arkeologi Maluku, 2007)
Famous Moluccas Archipelago as its heaven is mace, this matter cause commers activity in this archipelago region like fun, since early recognizing of commerce till a period to its top when Arab merchant, Chinese, and Europe enter this region, noise Avtivities commerce, not even unrightiously is foreign but also commerce in internal scope (local). Local Activities Commerce depict transfer noise (intersection) commodity of among commercial area which is one with other commercial area in region of coastal area in Moluccas archipelago scope. Local trade also depict activities exchange commodity of among coastal area and hinterland. In archaeology study, foreign ceramic data can play role to depict that matter. This matter remember foreign finding ceramic is not even found in seaboard of found also in sies archaeology in this area hinterland. This study is goods transfer of between seaboard with hinterland can be tracked.